Crystallization and preliminary crystallographic analysis of defective pollen wall (DPW) protein from Oryza sativa. Issue 6 (1st June 2014) - Wang, Wei; Ma, Yuanyuan; Suo, Yang; Yan, Liming; Zhang, Dabing; Miao, Chen
<x xml:space="preserve">Abstract</x> The defective pollen wall (dpw) gene of Oryza sativa encodes a fatty acid reductase (DPW) which plays important roles in primary fatty alcohol synthesis. DPW catalyzes the synthesis of 1‐hexadecanol. The enzyme shows a higher specificity for palmitoyl‐ACP than for palmitoyl‐CoA as the substrate, and can only use NADPH as the cofactor. To gain an understanding of the molecular mechanism underlying the reaction catalyzed by DPW, the gene encoding DPW without the N‐terminal 80 amino acids (DPWΔ80) was cloned into pET‐28a vector and was overexpressed in Escherichia coli. DPWΔ80 was purified to homogeneity and screened for crystallization. DPWΔ80 in complex with NADPH produced crystals that diffracted X‐rays to a resolution of 3.4 Å. The crystals belonged to space group P61 or P65, with unit‐cell parameters a = b = 222.8, c = 114.0 Å, α = β = 90, γ = 120°.